Sample manipulation and sample introduction techniques for inductively coupled plasma-atomic emission spectrometry and inductively coupled plasma-mass spectrometry - Anderson, Stanley Thomas George (My University, 1994)
Alternative sample manipulation and sample introduction methods for inductively coupled plasma-atomic emission spectrometry (ICP-AES) and inductively coupled plasma-mass spectrometry (ICP-MS) have been investigated. The broad objectives of the study were to broaden the scope and improve the analytical performance of the techniques. The methods which were investigated were: 1) Laser ablation. This technique was used only in combination with ICP-MS. The technique was not applied to ICP-MS because the laser ablation system is dedicated to the ICP-MS instrument. The laser ablation system was applied to the direct analysis of solid refractory materials, without dissolution of the sample. The main advantages of avoiding the dissolution step are that the sample preparation is rapid, there is no dilution or contamination of the sample, and no loss of volatile analyte elements. The problems which were encountered with the use of laser ablation were firstly, poor precision of measurement relative to solution analysis due to sample particles of widely varying size entering the plasma, and secondly, memory effects when changing from one sample type to another. 2) Flow injection. This sample manipulation method was used in combination with pneumatic nebulization for ICP-AES and ICP-MS. The technique was applied to a number of different analytical problems, with the objectives of speeding up analysis times, increasing the matrix tolerance of the instruments, and automating a variety of sample preparation processes. 3) Hydride generation. This technique was applied to the determination of arsenic and selenium by ICP-AES and ICP-MS, using a novel type of gas, liquid separator. The advantages of the technique were the separation of the analyte elements from interfering matrix species, and increased analyte sensitivity due to the excellent transport efficiency of hydride generation relative to solution nebulization. Numerous advantages have been obtained from the application of these sample manipulation and sample introduction techniques. Methods have been developed for the analysis of materials which are not suited to conventional solution nebulization, and the techniques have been used to improve the efficiency of analysis, to achieve lower detection eliminate, and to eliminate interferences.
A thesis submitted to the faculty of science, university of the Witwatersrand, Johannesburg,in fulfilment of the requirements for the degree of Doctor of Philosophy, 1994
Keywords: Atomic emission spectroscopy; Plasma spectroscopy; Plasma Spectrometry